2006
DOI: 10.1002/dys.301
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on reading difficulties in boys and girls: the Colorado twin study

Abstract: To test the hypothesis that the genetic etiology for reading disability may differ in males and females, data from identical and fraternal twin pairs were analysed using both concordance and multiple regression methods. The sample included 264 identical (129 male, 135 female) and 214 same-sex fraternal (121 male, 93 female) twin pairs in which at least one member of each pair had reading difficulties. The difference between the identical and fraternal twin pair concordance rates was slightly larger for females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 15 publications
(25 reference statements)
5
41
0
Order By: Relevance
“…The heritability of reading difficulties ranges from 30 to 72% (DeFries and Gillis 1993; Wadsworth et al 2000;Harlaar et al 2005;Hawke et al 2006;Wadsworth et al 2007). Genes influencing reading are distributed throughout the genome, with evidence for linkage of RD, reading skills or related phenotypes reported to at least 10 chromosome regions (Paracchini et al 2007;Scerri and Schulte-Korne 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The heritability of reading difficulties ranges from 30 to 72% (DeFries and Gillis 1993; Wadsworth et al 2000;Harlaar et al 2005;Hawke et al 2006;Wadsworth et al 2007). Genes influencing reading are distributed throughout the genome, with evidence for linkage of RD, reading skills or related phenotypes reported to at least 10 chromosome regions (Paracchini et al 2007;Scerri and Schulte-Korne 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Although this study suggests possible sex differences, it does not consider age as a factor and differs from the present study on several methodological factors such as age of sample, data collection by phone, and specific reading measures. A recent study by Hawke et al (2006) reported that the heritability of reading difficulties did not differ significantly by sex across the age range of the sample for a discriminant function score comprised of Peabody Individual Achievement Test (PIAT) reading recognition, reading comprehension and spelling subtests. Moreover, they reported that the interaction of zygosity, sex, and age was not significant.…”
mentioning
confidence: 98%
“…The TOWRE is quick to administer and makes it a preferred test among experimental researchers, particularly in studies involving testing of very large numbers of children. As an exemplar, TOWRE has been used in a large multinational longitudinal twin research including Australian children, exploring the interrelation of genetics and environment in early literacy development (Byrne et al, 2006;Hawke, Wadsworth, & DeFries, 2005). In several large studies, one or both TOWRE subtests were the only reading-accuracy tests used (Harlaar, et al, 2005).…”
Section: Methodsmentioning
confidence: 99%